GROWTH, YIELD AND QUALITY OF FRENCH BEAN (PHASEOLUS VULGARIS L.) AS INFLUENCED BY SULPHUR AND BORON APPLICATION ON INCEPTISOLS OF KASHMIR - A. GANIE, MUMTAZ; AKHTER, FARIDA; M. A. BHAT; G. R. NAJAR (The Bioscan, 2014)
An experiment was conducted during Kharif 2011 to study the response of french bean to different levels of sulphur and boron. The treatment combination of S45B1.0 recorded significantly higher values for nodulation parameters like number of nodules, their fresh and dry weight, dry matter accumulation at flowering, pod picking and harvesting stages, pod yield, yield attributes like number of pods plant-1, number of seeds pod-1 and test weight, seed yield, stover yield and protein content. The percent increase in these parameters over control was observed to be 210.90, 150.11, 164.88, 83.85, 61.55, 35.01, 42.33, 93.13, 30.80, 12.14, 27.13, 40.82 and 28.70, respectively. From the study it was concluded that for realizing higher yield and quality of french bean on inceptisols under temperate conditions of Kashmir valley, the nutrient management may centre around 45 and 1.0 kg ha-1 of sulphur and boron respectively, along with the recommended fertilizer dose of N, P, K and FYM.